Interdisciplinary Glocal Service Learning - Enhancement of Students' Interdisciplinary Competence, Self-Awareness and Glocal Civic Activism - Mirjam Braßler (Forum Neue Medien in der Lehre Austria, 2018)
Today we live in an increasingly interconnected and global world. There is an urgent need to solve global issues. Therefore, civic education ought to go beyond local community service. "Interdisciplinary glocal service-learning" is a novel combination of different teaching-learning methods such as service-learning, glocal learning, interdisciplinary learning, and education for a sustainable development. A pre-test - posttest study was conducted on a sample of 86 students participating in an interdisciplinary glocal service-learning course with a cohort of 140 students participating in traditional monodisciplinary courses at the same level in different departments (including Psychology, Economics, Education, and Geography students). As expected, students' development of interdisciplinary competence, self-awareness, and glocal civic activism was higher in interdisciplinary glocal service-learning.